Valuing community development through the social inclusion programme (SICAP) 2015-2017: Toward a framework for evaluation - Adele Whelan; Séamus McGuinness; Judith M. Delaney (The Economic and Social Research Institute (ESRI), 2019)
This ESRI research outlines the challenges of evaluating the impact of community development programmes, specifically focusing on the interventions with Local Community Groups (LCGs), as part of the Social Inclusion and Community Activation Programme (SICAP).
Keywords: 330